Critical evaluation of in natura sashimi products quality during Covid-19 pandemic (Research, Society and Development, 2024)
To emphasize the importance of quality food for health and immunity during COVID-19, this study evaluated raw fish quality from oriental cuisine delivery. From 75 orders, 29 samples of sashimi (salmon and tuna) suggested some deterioration, being subjected to quality analyses (pH, TVB-N, NH3, H2S, TBARs and biogenic amines). pH values varied between 5.7 to 8.4 in salmon and 5.4 to 6.6 in tuna. The values in salmon and tuna for TVB-N (between 10.00 and 40.00 mg/100gN), histamine (0.00 and 7.50 µg/g) and cadaverine (0.00 and 15.00 µg/g) was presented, respectively. Ammonia and H2S appeared in 93.1 and 31 % for salmon, and 15.8 and 10.5 % for tuna, respectively. while the lipid oxidation average was 0.60 and 1.14 mg MAEq /kg, respectively From the results obtained, refrigeration and freezing are essential for handling raw fish, preserving freshness, ensuring safety, and extending shelf life. Clearly, results of fish quality has shown a lack of organization in food delivered system. For that, simple and inexpensive methods can used to evaluate fish quality. Thus, sanitary surveillance can improve systemic efficiency to protect public health to be prepared for future crisis events.